Fatigue following head and neck cancer radiotherapy: an unrecognized side effect of modern radiotherapy techniques? - Twomey, Rosie; Culos-Reed, S. Nicole; Millet, Guillaume Y.; Lau, Harold (Translational Cancer Research; Vol 6, Supplement 9 (December 14, 2017): Translational Cancer Research, 2017)
Radiotherapy (RT) is an integral part of the treatment of squamous cell carcinoma of the head and neck, and is delivered post-operatively or in the intact setting, often with concurrent chemotherapy. Specifically, intensity modulated radiotherapy (IMRT) is an advanced method of delivering three-dimensional conformal radiotherapy (3D-CRT) using multiple intensity levels across each radiation beam. The purpose is to maximise the intended dose to the target while constraining unwanted irradiation to local tissues. As such, IMRT has become the standard of care in head and neck cancer (HNC). Substantial symptom burden remains with IMRT (1), but the phase 3 PARSPORT trial demonstrated that parotid-sparing IMRT reduces xerostomia, a highly prevalent and debilitating late toxicity (2), and improves health-related quality of life (HRQL) vs. conventional 3D-CRT (3). However, analysis of adverse events showed that compared to 3D-CRT, IMRT actually increases the incidence of fatigue graded as at least moderate severity during and up to 8 weeks after RT (3). Alongside other critical organs, central nervous system (CNS) structures lie adjacent or in close proximity to the tumor in HNC, and can receive low to moderate radiation doses during IMRT, i.e., higher than delivered with 3D-CRT. In their recent contribution to the field (4), Ferris and colleagues expand on a dosimetry analysis of the PARSORT trial (5) and further implicate irradiation of non-target delineated CNS structures during IMRT, and acute fatigue in HNC (where acute refers to during and in the weeks after treatment).